Enhancing Public Awareness of the Designer Profession: Visual Communication Strategies in Instagram Campaigns - Prihatmoko, Setiyo; Setiyadi, Teguh (University of Science and Computer Technology, 2024)
In the rapidly evolving digital era, social media, particularly Instagram, has become a primary platform for visual communication. However, public awareness of the designer's role still needs to be improved. This study explores effective visual communication strategies for enhancing public awareness and understanding of the designer profession through social media campaigns. The methods used include data analysis from questionnaires collected from campaign-exposed audiences and applying descriptive and inferential statistical techniques to assess the relationship between campaign exposure and increased awareness. The study’s results indicate that visual elements, such as color palettes, typography, and narratives' storytelling, significantly influence audience engagement and their understanding of the designer profession. While the campaign successfully captured attention, a communication gap still needs addressing to improve its effectiveness. This research offers critical insights for designers and marketers in crafting more impactful social media campaigns. It underscores the necessity of a targeted approach to elevate public appreciation for the designer profession.